(3GdgOGjI ef GdVdGdI aj eYQaI GdhbJ hGdbHdI ef ZjQ Bdgs - (3TgGH GdOjf CHh GdYHGS CMeO Hf CMeO Hf SdGeI GdTGaYi GdbdjhHi (B1069(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi QSe Ydi UaMGJ GdhLhO bhGWY GdGOdI GdebOeI ai JYQja GdhbJ hGdbHdI heGjJHYgG CeG GdhbJ agh dZI eWdb GdReGf s
(3BNQgG (B:s
(3djYQa UMJg Ch aSGOg aEf de jaYd Pdc aUdGJg HGWdg CjVkG dCfg LGgd HeYQaI GdhbJ hGdbHdI hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3Gdadcs